Вредноста на калпротектин во асцит како дијагностички и прогностички маркер за спонтан бактериски перитонитис кај пациентите со црнодробна цироза - Личоска Јосифовиќ, Фана (Медицински факултет, УКИМ, Скопје, 2020)
Introduction. Spontaneous bacterial peritonitis (SBP) in patients with liver cirrhosis is a newly developed, spontaneous bacterial infection of sterile ascites fluid, in the absence of intraabdominal sources of infection or malignancy. The most sensitive indicator of diagnosis is when the polymorphonuclear cell count (PMNs) is ≥250 in 1 ml ascites fluid and/or when a bacterial strain is isolated in microbiological culture. Objectives. The objectives of our study were to determine the value of calprotectin level in ascites fluid as a diagnostic and prognostic marker for SBP in patients with cirrhosis of the liver, to compare the value of calprotectin in ascites in patients with SBP before the start of antibiotic therapy and on the 7th day of therapy and to determine whether there is a correlation between the value of calprotectin and the count of PMNs in ascites before and after antibiotic therapy. Materials and methods. This prospective analytical observational pilot study included 70 patients with liver cirrhosis and ascites, divided into two groups, SBP and non-SBP. The quantitative measurement of calprotectin in ascites was performed with the Quantum Blue Calprotectin Ascites (LF-ASC25) test. The test is designed to selectively measure calprotectin antigen (MRP8/14) with direct sandwich immunoassay. The ascites samples were diluted with Chase Buffer 1:5 and after 12 minutes incubation at room temperature, the test line signal intensity and the control line were quantitated with BÜHLMANN Quantum Blue®Reader. The collected data were processed using the SPSS 23 statistical software for Windows. Results. In our study the average value of calprotectin in EG was 1.5 ± 0.40 μg/mL, while in the CG was 0.4 ± 0.30 μg/mL. The difference between the mean values was statistically significant for p <0.05 (t-test = 12.70849; p = 0.000000). The mean value of calprotectin in ascites on the 7th day from the start of antibiotic treatment decreases significantly to 1.0 ± 0.6, and the difference between the mean values of calprotectin in ascites before and after antibiotic treatment was statistically significant for p <0, 05 (Wilcoxon Matched Pairs test, T = 5.00000; Z = 4.594930; p = 0.000004). During the analysis, we registered a positive strong statistically significant correlation between the value of calprotectin and the count of PMNs before and after antibiotic therapy (Pearson linear correlation, r = 0.7740; p = 0.000 v.s r = 0.8894, p = 0.000). Conclusion. The the average value of calprotectin in ascites of 1.50 μg / mL can reliably predict a the count of PMNs ≥250 / μL, and can be used as an alternative to other conventional methods for diagnosing SBP, with a sensitivity of 94.3% and the specificity is 62.5%. The determination of the value of calprotectin in ascites on the 7th day from the start of antibiotic treatment was significantly positively correlated with the count of after therapy and had prognostic significance in terms of the effectiveness of antibiotic treatment in patients with SBP. There was a strong positive statistically significant correlation between the value of calprotectin in ascites and the count of PMNs in ascites before and after antibiotic therapy. The count of PMNs in ascites is a significant predictor of calprotectin levels in patients with SBP. If the count of PMNs increase by one unit of measure, the value of calprotectin concentration increases by 0.687187 on average.
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Мери Трајковска.
Keywords: calprotectin, spontaneous bacterial peritonitis (SBP), PMNs, ascites, liver cirrhosis